Development of an Experimental Model of Metabolic Syndrome in Sprague Dawley Rat - Mohammad Saifur Rohman; Mifetika Lukitasari; Dwi Adi Nugroho; Widodo Nashi; Nur Ida Panca Nugraheini; Teguh Wahyu Sardjono (Research Journal of Life Science, 2017)
The study was designed to establish an experimental models of metabolic syndrome that adequately mimic metabolic syndrome criteria as determined by NCEP ATP III.Eighteen Male Sprague dawley rats, 2 - 3 months old were used in the study. Combination of high fat and high sucrose (HFHS) diet for eight weeks and streptozotocin (STZ) injection in the second week was administered to induce metabolic syndrome. The body weight and biochemical parameters (blood glucose, triglyceride, HDL-cholesterol) were measured every 2 weeks. The rats with blood glucose (>126mg/dL), triglyceride (TG) (>150mg/dL), high systolic blood pressure (≥140 mmHg), and reduced HDL levels (<40 mg/dL) confirmed presence NCEP-ATP III criteria of metabolic syndrome. The adiponectin level was analyzed by ELISA methods.Fasting blood glucose, triglyceride, and systolic blood pressure increased significantly (p<0.05) in HFHS group compared to that of NC group. Moreover, after 8 week a significant lower HDL level was observed in HFHS group compared to that of NC group. In addition, HFHS group showed a significantly lower adiponectin level compared to that of NC group.The combination of low doses of STZ (30mg/kg) and HFHS administration for 8 weeks could induce metabolic syndrome mimicking human criteria of metabolic syndrome.